Data Utilization and Evidence-Based Decision Making in the Health Sector : Survey of Three Indian States - Belay, Tekabe; Mbuya, Nkosinathi; Rajan, Vikram (World Bank, 2012)
Recently, there has been increased attention to data use in the international public health community. At the global level there have been major investments in data collection for public health programs. However, there is concern that such data are not being used. Data and information lack value unless they are used to inform decisions. Interventions that increase local demand for information and facilitate its use enhance evidence-based decision making. Data use therefore, is critical to improving the effectiveness and sustainability of the health system. Data quality is poor and use of available data is low in India's health sector. The current study focuses on issues of data use. It aims to shed light on how data are used for decision-making at different levels of the health sector in India and to highlight impediments to improved data utilization. This report is organized in five sections. The survey design, instruments and the data collection process will be described in the next section. Findings including measurement of data use, perceived data use issues, skills assessment of respondents and ranges of actual decision making are presented in section three. Section four presents a number of hypotheses and discusses their implications. The last section provides conclusions and recommendations.